EVALUATION OF THE ACUTE AND SUBCHRONIC TOXICITY STUDIES OF BARLERIA BUXIFOLIA LINN. IN ALBINO RATS - REDDY, MANOHAR; SUNDARARAJAN, RAJA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The fundamental reason for this examination was to look at the acute and subchronic toxicity studies of chloroform and methanol extracts of Barleria buxifolia Linn. (Acanthaceae) on creature models according to the OECD rules 407 and 425, respectively. Methods: In acute oral toxicity, study a single oral dosages of 5000 mg/kg body weight of chloroform and methanol extracts was given individually to rats and watched them for 2 weeks for the discovery of acute changes and for its mortality any. During acute oral toxicity study period, no mortality was seen without any signs of intense changes. Further, it was executed the subchronic toxicity of extracts. Barleria buxifolia extracts (chloroform and methanol) were independently given every day at dosages of 250 and 500 mg/kg body weight for 90 days to recognize the progressions any at subchronic poisonousness levels. Towards the finish of the experimentation the serum tests of trail creatures were gathered and watched for any progressions in haematological, biochemical and histopathological boundaries Results: All parameters of treated group were shown unaltered changes throughout the study period when compared with that of normal group. The outcomes propose that the oral organization of chloroform and methanol extracts of Barleria buxifolia did not raise any huge poisonous impacts when contrasted with that of control animals. Conclusion: Hence, the extracts may be safe for therapeutic use and as an alternative system of medicine.